A school-based health promotion programme to increase help-seeking for substance use and mental health problems: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Lubman, Dan; Berridge, Bonita; Blee, Fiona; Jorm, Anthony; Wilson, Coralie; Allen, Nicholas; McKay-Brown, Lisa; Proimos, Jenny; Cheetham, Ali; Wolfe, Rory
Abstract Background Adolescence is a high-risk time for the development of mental health and substance use problems. However, fewer than one in four 16–24 year-olds with a current disorder access health services, with those experiencing a substance use disorder being the least likely to seek professional help. Research indicates that young people are keeping their problems to themselves or alternatively, turning to peers or trusted adults in their lives for help. These help-seeking preferences highlight the need to build the mental health literacy of adolescents, to ensure that they know when and how to assist themselves and their peers to access support. The MAKINGtheLINK intervention aims to introduce these skills to adolescents within a classroom environment. Methods/design This is a cluster randomised controlled trial (RCT) with schools as clusters and individual students as participants from 22 secondary schools in Victoria, Australia. Schools will be randomly assigned to either the MAKINGtheLINK intervention group or the waitlist control group. All students will complete a self-report questionnaire at baseline, immediately post intervention and 6 and 12 months post baseline. The primary outcome to be assessed is increased help-seeking behaviour (from both formal and informal sources) for alcohol and mental health issues, measured at 12 months post baseline. Discussion The findings from this research will provide evidence on the effectiveness of the MAKINGtheLINK intervention for teaching school students how to overcome prominent barriers associated with seeking help, as well as how to effectively support their peers. If deemed effective, the MAKINGtheLINK programme will be the first evidence-informed resource that is able to address critical gaps in the knowledge and behaviour of adolescents in relation to help-seeking. It could, therefore, be a valuable resource that could be readily implemented by classroom teachers. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR):ACTRN12613000235707 . Registered on 27 February 2013.